2022
DOI: 10.53819/81018102t4029
|View full text |Cite
|
Sign up to set email alerts
|

Role of Credit Access Program on the Performance of Women Owned MSES Incubated at KIRDI

Abstract: Women owned Micro and Small Enterprises (MSEs) are a source of employment and wealth creation in most of the world economies and Kenya not an exemption. However, the survival rate of the women owned MSEs is minimal. The main objective of the study was to evaluate the role of credit access program on the performance of women owned MSEs which have been incubated at KIRDI. The study was a survey study design. The target population was 259 MSE women entrepreneurs who have graduated from KIRDI business incubation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Kinya et al (2018) also reported the performance evaluation processes that Kenyan incubators undergo to assess how they support entrepreneurial ventures. Likewise, other studies examined the impact of credit access programs on the performance of women-owned micro and small enterprises incubated at the Kenya Industrial Research and Development Institute (KIRDI) (Waweru et al 2022). In Rwanda, family business formation has its roots in a quest to find economic opportunities among the marginalised communities in a post-conflict era.…”
Section: The Business Incubation Family Business Nexus In Africa-an O...mentioning
confidence: 99%
See 3 more Smart Citations
“…Kinya et al (2018) also reported the performance evaluation processes that Kenyan incubators undergo to assess how they support entrepreneurial ventures. Likewise, other studies examined the impact of credit access programs on the performance of women-owned micro and small enterprises incubated at the Kenya Industrial Research and Development Institute (KIRDI) (Waweru et al 2022). In Rwanda, family business formation has its roots in a quest to find economic opportunities among the marginalised communities in a post-conflict era.…”
Section: The Business Incubation Family Business Nexus In Africa-an O...mentioning
confidence: 99%
“…Some evidence equally suggests that family businesses can benefit from incubator services. It is claimed that incubators help entrepreneurs gain credibility (Waweru et al 2022) and build credible networks that help firms leverage internal and external network resources for business success. Several researchers have also claimed that business incubators serve as vehicles for small business development (Ojiagu and Ezemezuo 2023).…”
Section: Can Family Businesses Benefit From Business Incubation?mentioning
confidence: 99%
See 2 more Smart Citations